2017
DOI: 10.1038/s41598-017-06224-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defects controlled by preparation condition and heat treatment on the ferromagnetic properties of few-layer graphene

Abstract: Magnetism in graphene has stimulated extensive studies to search for novel metal-free magnetic device. In this paper, we use a synthesis method far from equilibrium state named self-propagating high temperature synthesis (SHS) to produce few-layer graphene with different defect contents and then use a heat treatment process (vacuum-annealing and air-cooling) to further control the defects in graphene. We find that the type and content of defects in graphene can be controlled by adjusting the mole ratio of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…93 The presence of structural defects breaks the symmetry of the graphene p orbital, which induces a band gap in graphene. 94,95 Park et al annealed graphene at 800 C under an argon atmosphere. The annealed graphene showed ferromagnetic behavior with a Curie temperature of 220 K in comparison to pristine graphene which was paramagnetic.…”
Section: Temperature-tuned Ferromagnetismmentioning
confidence: 99%
“…93 The presence of structural defects breaks the symmetry of the graphene p orbital, which induces a band gap in graphene. 94,95 Park et al annealed graphene at 800 C under an argon atmosphere. The annealed graphene showed ferromagnetic behavior with a Curie temperature of 220 K in comparison to pristine graphene which was paramagnetic.…”
Section: Temperature-tuned Ferromagnetismmentioning
confidence: 99%
“…Y Zhang et al through experiments found that graphene with single carbon atom defects can show paramagnetism [5]. Q H Miao et al prepared graphene by high-temperature synthesis, and found that the magnetism of graphene can be controlled by the defect concentration [6]. Experiment and theory are inseparable.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for the synthesis of graphene and few-layer graphene in [18,19] the classical SHS process was used, using calcium carbonate (CaCO 3 , 99.5%) and magnesium Mg to carry out the SHS reaction. Carbamide (CO(NH 2 ) 2 , 99.5%) and carbon dioxide (purity 99.9%) were used as the carbon source.…”
Section: Introductionmentioning
confidence: 99%